Case study: Optimisation of Federal Land Development Authority Jengka supply chain management using P-graph approach - Haleem, A.A. (Italian Association of Chemical Engineering - AIDIC, 2015)
Establishment of biomass supply chain is preliminary stage for biomass energy production especially in proposing potential processing plant location. Most of the relevant biomass is produced in abundance in agriculture sector. In Malaysia, biomass supply is obtained mainly from oil palm plantation which governed under Federal Land Development Authority. Biomass supply chain deals with harvesting, storage, pretreatment and transportation. Low energy density of biomass combined with availability of biomass that is widely distributed contributes huge constraints to the problem. To address this issue, P-graph modelling is used as the methodology to solve combinatorial complexity of the biomass supply chain in Federal Land Development Authority Jengka. Few possible locations for building new biomass processing plant and storage hubs were introduced in the optimisation problem. Existing plant mills, hubs and possible plant locations were interconnected to create a network. Fuel consumption for transportation was calculated by taking into account the road profiles of the routes in Jengka. The resulting solution from Accelerated Branch and Bound algorithm in P-graph shows that the optimal solution is through building new plant in location 1, 2 and 4 for a profit of 77.35 M MYR/y (18.3 M â¬/y). Copyright Â© 2015, AIDIC Servizi S.r.l.,.